Effects of various interventions on non-alcoholic fatty liver disease (NAFLD): A systematic review and network meta-analysis - Xinchen Wang; Xiaoqian Jin; Hancheng Li; Xianyu Zhang; Xi Chen; Kuan Lu; Chenliang Chu (Frontiers Media S.A., 2023)
Background: With the increasing prevalence of obesity and metabolic syndrome, the incidence of non-alcoholic fatty liver disease (NAFLD) is also increasing. In the next decade, NAFLD may become the main cause of liver transplantation. Therefore, the choice of treatment plan is particularly important. The purpose of this study was to compare several interventions in the treatment of NAFLD to provide some reference for clinicians in selecting treatment methods.Methods: We searched Public Medicine (PubMed), Medline, Excerpta Medica Database (Embase), and Cochrane Library from January 2013 to January 2023 to identify randomized controlled trials (RCTs) published in English. The network meta-analysis was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Forty-three studies accounting for a total of 2,969 patients were included, and alanine aminotransferase (ALT), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL) were selected as outcome measures for analysis and comparison.Results: We evaluated the results of drug, diet, and lifestyle interventions between the intervention and control groups. Curcumin (CUN) and probiotics (PTC) were selected for medication, the Mediterranean diet (MDED) was selected for special diet (SPD), and various kinds of exercise and lifestyle advice were selected for lifestyle interventions (LFT). The SUCRA was used to rank interventions according to the effect on ALT indicators (SUCRA: PTC 80.3%, SPD 65.2%, LFT 61.4%, PLB 32.8%, CUN 10.2%), TC indicators (SUCRA: PTC 89.4%, SPD 64%, CUN 34%, LFT 36.6%, PLB 17%), and LDL indicators (SUCRA: PTC 84.2%, CUN 69.5%, LFT 51.7%, PLB 30.1%, SPD 14.5%). The pairwise meta-analysis results showed that MDED was significantly better than NT in improving ALT [SMD 1.99, 95% CI (0.38, 3.60)]. In terms of improving TC and LDL, ATS was significantly better than NT [SMD 0.19, 95% CI (0.03, 0.36)] [SMD 0.18, 95% CI (0.01, 0.35)].Conclusion: Our study showed that PTC is most likely to be the most effective treatment for improving NAFLD indicators. Professional advice on diet or exercise was more effective in treating NAFLD than no intervention.